Pengaruh Disiplin Kerja Terhadap Kinerja Karyawan Pada PT. Daya Mitra Serasi Cabang Pekanbaru - Rina Sundari (Eko dan Bisnis: Riau Economic and Business Review, 2025)
This research was conducted at PT. Daya Mitra Serasi Pekanbaru Branch located at Jalan Soekarno-Hatta No. 46 Sidomulyo Barat, Tampan District, Pekanbaru City, Riau. The purpose of this study was to determine the effect of work discipline on employee performance at PT. Daya Mitra Serasi Pekanbaru Branch. The research method used was descriptive with a quantitative approach. With a population of 32 employees. The sampling technique used was saturated sampling, namely the entire population represents the sample. The data analysis technique used was simple linear regression with a t-test hypothesis test. Based on the results of the t-test, the calculated t result was 7.006 > 2.042 with a significance of 5% (α = 0.05) or <0.005 so that the hypothesis Ha was accepted, namely work discipline had an effect on employee performance at PT. Daya Mitra Serasi Pekanbaru Branch. From the results of the simple linear regression test, there is a constant value (a) of 12.907, meaning that the work discipline variable (X) has a value of 0.702, then the dependent variable, namely performance (Y), has a value of 12.907, meaning that if the work discipline variable is increased by 1 unit, the performance variable (Y) will experience an increase of 0.702 units. From the results of the determination coefficient test, the R Square (R²) value is 0.621 if expressed as a percentage, namely 62.1%, meaning that work discipline (X) has a 62.1% effect on the performance (Y) of employees of PT. Daya Mitra Serasi Pekanbaru Branch, and 37.9% is influenced by other factors not included in this study.